Prayer of Jesus - Hanegraaff, Hank; Payne, Thomas (Nashville, TN : Tommy Nelson, 2002)
Presents one version of the Lord's prayer and explains in simple words what each line means.
Cover title.
On board pages.
Keywords: Juvenile works